1995
DOI: 10.1111/j.1365-3040.1995.tb00577.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in trace metal species and other components of the rhizosphere during growth of radish

Abstract: Changes in the properties of soil solution in the rhizosphere of developing radish plants were investigated. Variations in these properties were expected to affect the distribution and speciation of metals in the soil and soil solution. Applications of essential nutrients were linked to plant transpiration rates and prevented excess addition of nutrient ions, so that subtle changes in soil solution composition would not be obscured. Soil solution pH, the concentration of dissolved organic carbon (DOC) and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(27 citation statements)
references
References 33 publications
0
26
1
Order By: Relevance
“…The complexation of Mn 2+ by malate was also reported to increase its mobility and bioavailability in the rhizosphere by preventing Mn oxidation in an uncontaminated soil (Jauregui and Reisenauer, 1982). Further evidence for the complexation of free heavy metal ions by dissolved organic substances in the rhizosphere have been provided by Hamon et al (1995) (Figure 7.12), Lorenz et al (1997), and Legrand et al (2005).…”
Section: Impact Of Organic Substances On the Speciation Of Trace Elemmentioning
confidence: 77%
“…The complexation of Mn 2+ by malate was also reported to increase its mobility and bioavailability in the rhizosphere by preventing Mn oxidation in an uncontaminated soil (Jauregui and Reisenauer, 1982). Further evidence for the complexation of free heavy metal ions by dissolved organic substances in the rhizosphere have been provided by Hamon et al (1995) (Figure 7.12), Lorenz et al (1997), and Legrand et al (2005).…”
Section: Impact Of Organic Substances On the Speciation Of Trace Elemmentioning
confidence: 77%
“…The application of chelating agents, e.g., EDTA, has been proved to enhance the translocation of metals from the root to shoot (Barber and Lee 1974;Hamon et al 1995;Vassil et al 1998;Gleba et al 1999;Safari Sinegani and Khalilikhah 2011). Despite significant changes in phytoextraction efficiency, in some researches, TF had not changed after treatment Safari Sinegani 2013, 2014).…”
Section: Effects Of Chelating Agents On Translocation Factors Of Metamentioning
confidence: 98%
“…Several authors (Cornu et al 2007b;Hamon et al 1995) propose that the integration of these temporal variations may improve the prediction of plant uptake. Our study confirmed this point as the Cd concentration in lettuce roots was more closely related to the root exposure to solution Cd (E Cd ) than to the initial concentration of Cd 2+ measured on day 0 (data not shown).…”
Section: Root CD Concentration Versus Root Exposure To Solution Cdmentioning
confidence: 99%